Quanutm dot metal nanoparticle based composites for biomedical applications - Gérard, Valérie (Trinity College (Dublin, Ireland). School of Chemistry, 2013)
The main aim of this project is to develop a range of nanocomposite materials based on gold and silver nanostructures and semiconductor nanoparticles, or quantum dots (QDs). The work involves the synthesis, functionalisation and combination of anisotropic metal nanoparticles and CdTe QDs. The new nano-composites are to be characterised and their behaviour in biological media is to be investigated.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.